(untitled) (London Journal of Research In Management & Business, 2025)
Effectively reducing the possible hazards connected with the facilitation of gender medical travel and tourism is the advancement of the artificial intelligence health system. The AI enhancement is to monitor and include the characteristics of medical journey from the initial location to the destination for treatment. Using a quantitative research technique (a survey research instrument and a PLS-SEM model), the study aims to enhance AI health systems to facilitate medical travel and tourism. 379 responders, including medical professionals, tourist experts, gender experts, and interested thinkers in AI health and technology, provided the data. According to the study findings, the AI health system of medical travel and tourism has significantly improved as a result of international medical legislation, cultural differences, safe medical destinations, and extended medical travel for gender people. In indicating AI while preserving the dignity of the holy site or the trip, the study raises the particular attention that religious travellers with gender basedmedical issues. Future research may concentrate on the expanded function of AI with particular emphasis to guarantee the honour and respect of the tourist location. For the best results from a reputable and secure gender vacation location, it is advised that AI deployment in the health system be centralized.